Assessing the ICT sector contribution to the millennium development goals: Status quo analysis of sustainability information for the ICT sector - Michael Kuhndt; Justus von Geibler; Martin Herrndorf (Wuppertal Institut für Klima, Umwelt, Energie, 2006)
Information and communiction technologies (ICTs), as a crosscutting evolving technology, can contribute to the achievement of the Millennium Development Goals (MDGs). This opinion is not only voiced by business, but also expressed in specific MDG targets as well as from a range of stakeholders, e.g. NGOs, intergovernmental organisations and financial institutions. However, ICT implications are not only beneficial, a range of stakeholders raises critical issues. Quantified information on ICT contribution to the MDGs available today on both micro and macro level does not meet the expectations. Business actors thus need solid and balanced sustainability information to accurately get the implications of ICT and to promote and assess their voluntary activities. In this context the project A Comprehensive Approach for Assessing Risks and Opportunities of the ICT sector and ICT applications addressed the contributions of the ICT sector to the achievement of the MDGs. The project's core objective has been to develop a discussion paper on the assessment of risks and opportunities of ICT. The scope of the paper is to raise awareness for a balanced approach of sustainability information (regarding the contribution to the MDGs, at micro and macro level, risks and opportunities) and to provide best practice examples for a comprehensive approach in the ICT sector. Therefore, research questions have been addressed such as: How can ICT contributions to the MDGs be quantified? What are the demands on sustainability information for the ICT sector? What are the business implications from this? – – nformations- und Kommunikationstechnologien (ICT) können als Schlüsseltechnologien einen Beitrag zur Erreichung der UNO Millennium Entwicklungsziele (Millennium Development Goals - MDGs) leisten. Diese Meinung kann man nicht nur ihren einzelnen Teilzielen entnehmen, sondern sie wird auch von Seiten der Wirtschaft und einigen Interessengruppen vertreten. Aber die Beiträge des ICT-Sektors werden nicht nur positiv gesehen. Es gibt durchaus kritische Stimmen. Quantifizierte Informationen als Beitrag der ICT zu den MDGs, die derzeit auf Mikro- und Makroebene verfügbar sind, entsprechen nicht immer den Anforderungen von Interessengruppen. Daher benötigen Unternehmen solide und ausgewogene Nachhaltigkeitsinformationen, um ihren Einfluss ausreichend zu erfassen sowie freiwillige Aktivitäten zielgerichtet umsetzen zu können. Das Ziel des Forschungsprojektes Comprehensive Approach for Assessing Risks and Opportunities of the ICT sector and ICT Applications war die Entwicklung eines Diskussionspapiers zu den Chancen, Risiken und Anwendungen von ICT. Das Papier soll ein Bewusstsein für die Ausgewogenheit von Nachhaltigkeitsinformationen (in Bezug auf die Zielsetzung von MDGs auf Mikro- und Makroebene) schaffen und Beispiele für fortschrittliche Ansätze zur Messung von Nachhaltigkeitsinformationen im ICT-Sektor darstellen. Dazu wurden eine Reihe von Forschungsfragen bearbeitet wie z. B.: Wie können die Beiträge der Informations- und Kommunikationstechnologie (ICT) zu den Millennium Development Goals (MDGs) gemessen werden? Was sind die Anforderungen an Nachhaltigkeitsinformationen für den ICT-Sektor? Welche Implikationen ergeben sich für einzelne Akteure des ICT-Sektors?
urn:nbn:de:bsz:wup4-opus-25086
Keywords: 380